2021
DOI: 10.1038/s41598-021-96488-0
|View full text |Cite
|
Sign up to set email alerts
|

Su(Hw) primes 66D and 7F Drosophila chorion genes loci for amplification through chromatin decondensation

Abstract: Suppressor of Hairy wing [Su(Hw)] is an insulator protein that participates in regulating chromatin architecture and gene repression in Drosophila. In previous studies we have shown that Su(Hw) is also required for pre-replication complex (pre-RC) recruitment on Su(Hw)-bound sites (SBSs) in Drosophila S2 cells and pupa. Here, we describe the effect of Su(Hw) on developmentally regulated amplification of 66D and 7F Drosophila amplicons in follicle cells (DAFCs), widely used as models in replication studies. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…Consistent with previous research on BEAF32 IBP indirect chromatin binding 7 , we show that indirect binding of Su(Hw) to chromatin can re ect the long-range chromatin interactions in which Su(Hw) participates. Previously, we identi ed a cluster of indirect Su(Hw) ChIP-Seq peaks in Drosophila ovaries that contain a GTGT-motif instead of the Su(Hw) DNA-binding motif 17 . Here, we found that these indirect Su(Hw) peaks are occupied by Combgap, a protein known to recruit PcG group proteins to chromatin 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with previous research on BEAF32 IBP indirect chromatin binding 7 , we show that indirect binding of Su(Hw) to chromatin can re ect the long-range chromatin interactions in which Su(Hw) participates. Previously, we identi ed a cluster of indirect Su(Hw) ChIP-Seq peaks in Drosophila ovaries that contain a GTGT-motif instead of the Su(Hw) DNA-binding motif 17 . Here, we found that these indirect Su(Hw) peaks are occupied by Combgap, a protein known to recruit PcG group proteins to chromatin 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Our ChIP-Seq data from wild-type and Su(Hw) LOF Drosophila ovaries con rmed this observation. We showed that direct Su(Hw) ChIP-Seq peaks can be classi ed into two clusters: those enriched with FAIRE signal and active chromatin proteins (Su(Hw) direct FAIRE + peaks), and those lacking these features (Su(Hw) direct FAIRE-peaks) 17 . In situ Hi-C experiments demonstrated that both Su(Hw)-dependent LRIs and domain border insulation are only characteristic of Su(Hw) direct FAIRE + peaks (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations